TELERA—Asynchronous TELEmedicine for Patients With Rheumatoid Arthritis: Study Protocol for a Prospective, Multi-Center, Randomized Controlled Trial - Mucke, Johanna; Knitza, Johannes; Muehlensiepen, Felix; Grahammer, Manuel; Stenzel, Ramona; Simon, David; Kleyer, Arnd; Krönke, Gerhard; Sharp, Charlotte; Bendzuck, Gerlinde; Korinth, Marianne; Elling-Audersch, Corinna; et al. (Frontiers in Medicine, 2021)
Innovative strategies are needed to adequately assess and monitor disease activity of patients with rheumatoid arthritis (RA) in times of scarce appointments. The aim of the TELERA study is to evaluate the feasibility and performance of asynchronous telemedicine visits based on patient-generated data and patient’s drug history. RA patients use a medical app, ABATON, that captures the results of a self-performed quick CRP-test, joint-count, and electronic patient-reported outcomes in between visits. This is a prospective, multi-center, randomized controlled trial performed in four German university centers. The estimated sample size is 120 patients. The main outcome is the agreement of rheumatologists’ treatment decisions based on asynchronous telemedicine patient-generated data with traditional in-person rheumatology clinic-based decisions and with patient suggestions. The TELERA trial will provide evidence regarding the implementation of remote care in rheumatology. Clinical Trial Registration: This clinical trial was registered at German Registry for Clinical Trials (DRKS), main ID: DRKS00024928, URL: http://www.drks.de/DRKS00016350.